Peace Education Implementation for Young Interfaith Peace Community (YIPC) of Malang - Ja'far, Handoko; Firmita Dewi Safira, Aura (CV Kalimasada Group, 2023)
This study aims to obtain information related to the urgency and variety of activities associated with the implementation of peace education for the young interfaith peace community of Malang. This research is mixed-methods research, which is a combination of qualitative and quantitative research methods with a descriptive approach. The subject of this study is a Muslim facilitator and participant in SIPC 2019. The data collection techniques used are questionnaires and documentation, and the data analysis used is explanatory sequential, then explained descriptively. The result of this research explains that peace education implementation for the YIPC of Malang is urgent for human relations reasons, and the peace goal includes the vulnerability of youth and interfaith potential. Young interfaith communities offer fertile ground for fostering tolerance, understanding, and collaborative problem-solving. Peace education for YIPC of Malang is implemented through several activities, including SIPC (Student Interfaith Peace Camp), regular meetings, and WIHW (World Interfaith Harmony Week).